2015
DOI: 10.1007/s00248-015-0571-1
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of Field-Caught and Laboratory-Adapted Australian Tephritid Fruit Fly Species with Different Host Plant Use and Specialisation

Abstract: Tephritid fruit fly species display a diversity of host plant specialisation on a scale from monophagy to polyphagy. Furthermore, while some species prefer ripening fruit, a few are restricted to damaged or rotting fruit. Such a diversity of host plant use may be reflected in the microbial symbiont diversity of tephritids and their grade of dependency on their microbiomes. Here, we investigated the microbiome of six tephritid species from three genera, including species that are polyphagous pests (Bactrocera t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
112
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 64 publications
21
112
3
2
Order By: Relevance
“…Many of the genera found in the present study have not been found associated with the housefly before. Alpha diversity measures were also higher in the present study compared to other studies looking at the microbiota of arthropods [52,53,5961]. Average Chao1 ranged from 750 to 1,500 and Shannon diversity index from 3.4 to 5.4.…”
Section: Discussioncontrasting
confidence: 58%
“…Many of the genera found in the present study have not been found associated with the housefly before. Alpha diversity measures were also higher in the present study compared to other studies looking at the microbiota of arthropods [52,53,5961]. Average Chao1 ranged from 750 to 1,500 and Shannon diversity index from 3.4 to 5.4.…”
Section: Discussioncontrasting
confidence: 58%
“…Depending on availability, these were adults (females or males) and/or nymphs (fourth or fifth instar) from one to up to seven populations. All specimens were surface sterilised with 4% sodium hypochlorite as described in Morrow et al [44], and DNA was extracted from whole individuals using DNeasy 96 Blood and Tissue kit (Qiagen) including RNase treatment with 0.4 mg RNase (Sigma). DNA quality and yield was assessed by Nanodrop spectrophotometry, Qubit 2.0 Fluorometry and gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Extracts of high molecular weight and amplifiable DNA were submitted to the HIE Next Generation Sequencing Facility for 16S rRNA gene amplification using primers 341F and 805R, which encompass the V3–V4 region of the 16S rRNA gene and produce a fragment of approximately 464 bp, including primers [44]. Library preparation, inputting 7 ng of DNA extract, was performed using the Nextera XT kit and 2 × 300 bp paired-end sequencing on a 384-multiplexed Illumina MiSeq run.…”
Section: Methodsmentioning
confidence: 99%
“…5 and 6). It seems possible that Photorhabdus might naturally encounter Enterococcus, since Enterococcus species have been found in the digestive tracts of wild-caught insects (65,(69)(70)(71)(72). EDITS production might be an important way in which Photorhabdus spp.…”
Section: Discussionmentioning
confidence: 99%